1998
DOI: 10.4278/0890-1171-13.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preferences in Format and Type of Community-Based Weight Control Programs

Abstract: These data suggest that some community members will get interested and take part in low-cost, minimal contact programs for exercise and weight control. Future research efforts should focus on investigating ways to increase participation in brief or minimal contact programs, particularly among groups that may be difficult to reach and at high risk for the development of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 12 publications
1
52
0
Order By: Relevance
“…Participants could participate in a face-to-face weight control short course conducted by a health educator, aerobics classes, group walks, exercise seminars, a one-month membership of exercise facilities with free childcare, a correspondence weight control course, a marathon, a recipe contest, and the`5&3' Challenge, in which participants were challenged to exercise at least 20 min and to eat ®ve servings of fruit andaor vegetables on a minimum of 3 days per week. 44 Fitzgibbon, Stolley et al 40,46 reported two interventions among African-American mothers and daughters aimed at obesity prevention by dietary change. During the 6-week pilot-study, 40 weekly one-hour meetings led by a clinical psychologist or a graduate clinical psychology student took place.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Participants could participate in a face-to-face weight control short course conducted by a health educator, aerobics classes, group walks, exercise seminars, a one-month membership of exercise facilities with free childcare, a correspondence weight control course, a marathon, a recipe contest, and the`5&3' Challenge, in which participants were challenged to exercise at least 20 min and to eat ®ve servings of fruit andaor vegetables on a minimum of 3 days per week. 44 Fitzgibbon, Stolley et al 40,46 reported two interventions among African-American mothers and daughters aimed at obesity prevention by dietary change. During the 6-week pilot-study, 40 weekly one-hour meetings led by a clinical psychologist or a graduate clinical psychology student took place.…”
Section: Search Resultsmentioning
confidence: 99%
“…36 ± 46 Seven interventions were undertaken in the USA, and two in Italy. Two papers referred to an intervention with African-American mothers and daughters, 40,46 two papers to the Pound of Prevention study, 43,44 and two papers to the Pathways study. 36,42 Four interventions took place in the community 40,41,43,44,46 and ®ve were schoolbased.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations